Catalogue of oribatid mites (Acari: Oribatida) from Argentina - Fredes, Natalia A. (Zootaxa, 2018)
A catalogue of oribatid mites recorded in Argentina is provided here. This catalogue includes a total of 398 described species comprised in 185 genera and 75 families. For each species synonymies, global and local distributions as well as general remarks are provided. It also includes 13 new combinations and 17 new synonyms.